Feminist jurisprudence in Islam: an overview - Ansari, Abdul Haseeb (Serials Publications, 2010)
Feminism is not new to Islam. It gave due respect to women in their houses and in the society. It granted them rights which were those days strange in the West. Many rights that Islam granted to women in different capacities were achieved by women after several decades-long feminist movements in different parts of the world. Women there are still struggling for ensuring rights that laws have given to them. In the West, women are still struggling for eradication of discriminatory laws and honourable treatments at the place of work and in the society. On the contrary, women’s rights and duties in Islam, which are mostly based on divine wisdom, treat women at par with men. In certain cases, where women have been discriminated, Islam, in fact, has given a favour to them. However, on the ground, especially in South Asian and African countries, in certain spheres of social life, women do not get proper treatment; their rights are either ignored or given least importance. In this paper, some of these grey areas have been discussed and viable solutions to them have been suggested.